Peran guru dalam membentuk karakter dan membangun hubungan sosial di sekolah - Ghifarix, Herfanda Agif; Khasanah, Nur (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
This study aims to analyze the role of teachers in shaping students' character and building social relationships in the school environment through a library research approach. Teachers have a strategic function as educators, mentors, and role models in internalizing moral, social, and emotional values to students. This literature review uses relevant sources from educational books, scientific articles, and previous research results that discuss the social and educational roles of teachers. The results of the study show that teachers play an important role in character building through habit formation, modeling, and empathetic communication in social interactions. In addition, harmonious social relationships between teachers and students have been proven to strengthen a positive school climate and improve the success of the learning process. This study confirms that the quality of teacher interactions is the main foundation for character building and social networks in schools.